Glass cutting UV visbreaking adhesive and preparation method thereof
By using synergistic effects of raw materials such as methacrylic acid, acrylate monomer and epoxy acrylate, the problem of complex preparation and difficulty in achieving high initial viscosity and post-UV detrimentation in the prior art is solved, and efficient glass cutting UV detrimentation adhesive is achieved.
Patent Information
- Application Number
- CN202510204899.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-06-10
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives, and specifically relates to a glass cutting UV viscosity-reducing adhesive and a preparation method thereof. Background Art
[0002] Pressure-Sensitive Adhesive (PSA) is a functional material that can achieve bonding with slight pressure at room temperature. It is currently widely used in medical dressings, electronic packaging, labels, industrial tapes, etc. The bonding strength of traditional pressure-sensitive adhesives usually depends on the physical entanglement of molecular chains and the interaction of polar groups, but it needs to be pasted repeatedly, so its application is relatively limited.
[0003] Viscosity-reducing pressure-sensitive adhesives achieve dynamic regulation of bonding strength by introducing controllable chemical or physical mechanisms. The core value of viscosity-reducing pressure-sensitive adhesives lies in their "on-demand bonding and peeling" characteristics. In the medical field, it can avoid secondary damage to the skin or wounds when traditional tapes are torn off; in the manufacture of electronic products, after temporarily fixing precision components, they can be peeled off without residue by heating or light, improving production efficiency and yield; in the field of environmentally friendly packaging, the viscosity-reducing design can promote the separation of the adhesive layer and the substrate and improve the material recovery rate. In addition, some viscosity-reducing adhesives can achieve repeated bonding while maintaining the initial bonding strength by regulating the molecular structure, thus expanding the application scenarios. Compared with traditional pressure-sensitive adhesives, viscosity-reducing pressure-sensitive adhesives have a wider range of applications.
[0004] Chinese patent application CN110628333A discloses a viscosity-reducing pressure-sensitive adhesive, which mainly utilizes self-expanding microsphere foaming agent and sodium bicarbonate to control the closed-cell foaming of thick-layer PVC, thereby reducing the viscosity of the substrate surface after heating, making it convenient to remove the pressure-sensitive adhesive after heating. However, its preparation raw materials are relatively complex, and it is difficult to simultaneously achieve the technical effects of high initial viscosity and post-UV viscosity reduction. Therefore, there is an urgent need for a new viscosity-reducing adhesive with simple raw materials, which has both high initial viscosity and post-UV viscosity reduction, so as to meet the application of more industrial production scenarios. Summary of the invention
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a glass cutting UV viscosity-reducing adhesive, the preparation raw materials of which, by weight, include: 1-5 parts of methacrylic acid, 300-500 parts of acrylate monomers, 40-80 parts of epoxy acrylate, 3-8 parts of initiator, 500-1000 parts of solvent, 5-20 parts of catalyst, and 0.1-1 part of inhibitor.
[0006] As an implementable case, the mass ratio of methacrylic acid, acrylate monomer and epoxy acrylate is (2-3): (350-420): (40-50).
[0007] As an implementable case, the acrylate monomer includes one or more of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, glycidyl acrylate, methyl methacrylate, ethylene glycol diacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate.
[0008] Further, the acrylate monomer includes n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate.
[0009] Further, the mass ratio of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate is (80 - 90):(200 - 240):(30 - 45):(50 - 75):(10 - 30).
[0010] As an implementable case, the epoxy acrylate includes one or more of 3,4-epoxycyclohexylmethyl methacrylate, 1,2-epoxycyclohexylmethyl methacrylate, dicyclopentadiene epoxy methyl methacrylate, bisphenol A epoxy acrylate, and 3,4-epoxy tetrahydrofuran methyl methacrylate.
[0011] Further, the epoxy acrylate includes 3,4-epoxycyclohexylmethyl methacrylate.
[0012] Acrylate monomers such as n-butyl acrylate, isooctyl acrylate, and butyl methacrylate have good flexibility, enabling the adhesive to quickly wet the surface when contacting the adherend, increasing the contact area, and thus improving the initial adhesion performance. The introduction of 2-hydroxyethyl methacrylate provides reactive groups for the adhesive, helping to form chemical bonds with the functional groups on the surface of the adherend and further enhancing the initial adhesion. 3,4-epoxycyclohexylmethyl methacrylate has an epoxy group, which can undergo a cross-linking reaction with acrylate monomers in the adhesive to form a polymer with a three-dimensional network structure. Therefore, it can improve the cohesive strength of the adhesive, enabling it to better resist external force damage during initial adhesion, thereby enhancing the initial adhesion performance. Under UV light, the acrylate monomer, epoxy acrylate, and methacrylic acid will undergo a polymerization reaction to form a highly cross-linked network structure. After curing, it has high cohesive force, making the adhesive easier to detach from the surface of the adherend during peeling, thus achieving the effect of reduced adhesion and no residual glue. In addition, during the UV curing process of 3,4-epoxycyclohexylmethyl methacrylate, its epoxy group can cross-link with adjacent molecular chains to form a more stable network structure, which can also effectively inhibit the movement of molecular chains, reduce the interaction between the adhesive and the adherend, and thus reduce the peel strength, achieving the technical effect of reduced adhesion after UV light irradiation.
[0013] However, it is necessary to further define the mass ratio of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate. In the present invention, the mass ratio of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate is (80 - 90):(200 - 240):(30 - 45):(50 - 75):(10 - 30). If this limitation is not met, it will affect the flexibility of the adhesive, weaken the chemical bond with the adherend, and thus reduce the initial adhesion performance and the adhesion reduction performance.
[0014] As an implementable case, the initiator includes one or more of ammonium persulfate, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, and azobisisobutyronitrile.
[0015] Further, the initiator is benzoyl peroxide.
[0016] As an implementable case, the solvent includes one or more of toluene, dichloromethane, ethyl acetate, chloroform, acetone, and n-butanol.
[0017] Further, the solvent is ethyl acetate.
[0018] As an implementable case, the catalyst includes one or more of boron trifluoride, N,N-dimethylaniline, tetramethylthiourea, N,N-dimethylbenzylamine, 2-methylpyridine, and tetramethylammonium chloride.
[0019] Further, the catalyst is boron trifluoride.
[0020] Boron trifluoride is a strong Lewis acid that can react with the double bond in methacrylic acid and acrylate monomers to generate reactive intermediates, thereby accelerating the free radical polymerization reaction; at the same time, boron trifluoride can react with the epoxy group in 3,4-epoxycyclohexylmethyl methacrylate to promote the crosslinking reaction. By forming more crosslinking points, boron trifluoride can improve the cohesive strength and heat resistance of the adhesive, thereby enhancing the initial adhesion performance and the adhesion reduction performance of the adhesive.
[0021] As an implementable case, the inhibitor includes one of hydroquinone, p-methoxyphenol, hydroquinone, and methyl hydroquinone.
[0022] Further, the inhibitor is p-methoxyphenol.
[0023] The second aspect of the present invention provides a preparation method of a glass cutting UV adhesion reduction adhesive, including: first mixing methacrylic acid and acrylate monomers, and then adding epoxy acrylate, initiator, solvent, catalyst, and inhibitor for reaction to obtain it.
[0024] Further, the preparation method of the glass cutting UV adhesion-reducing adhesive includes:
[0025] S1. Mix methacrylic acid and acrylate monomers evenly to obtain a methacrylic acid and acrylate monomer mixture. Divide it into two equal parts on average. Take one part and put it into the bottom of the reaction kettle, add 30-38% of the total amount of the solvent and 35-40% of the total amount of the initiator, control the reaction temperature at 80-90°C, and keep the reaction for 2-5 hours;
[0026] S2. Then dropwise add the remaining methacrylic acid and acrylate monomer mixture and 30-34% of the total amount of the solvent, and the dropping time is 3-4 hours;
[0027] S3. Then dropwise add 3-5% of the total amount of the solvent and 35-40% of the total amount of the initiator, and the dropping time is 15-30 minutes. After the dropping is completed, keep the reaction at 80-90°C for 30-60 minutes;
[0028] S4. Then add 3-5% of the total amount of the solvent and 5-10% of the total amount of the initiator in one batch, and keep the reaction at 80-90°C for 1-2 hours;
[0029] S5. Then add 3-5% of the total amount of the solvent and 5-10% of the total amount of the initiator in one batch, and keep the reaction at 80-90°C for 3-4 hours;
[0030] S6. After the reaction is completed, add 4-5% of the total amount of the solvent, cool to 20-30°C, and place for 24-48 hours;
[0031] S7. Re-open the reaction kettle, heat up to 80-90°C, and sequentially add a polymerization inhibitor, epoxy acrylate, a catalyst and the remaining solvent, react for 8-12 hours. After the reaction is completed, cool to 20-30°C and discharge to obtain the product.
[0032] Beneficial effects
[0033] (1) Through the synergistic effect of methacrylic acid, acrylate monomers and epoxy acrylate, the adhesive has high initial tack before UV curing, can quickly wet the adhered surface and form a firm bond; after UV curing, the epoxy groups crosslink with acrylate to form a three-dimensional network structure, significantly reducing the peel strength and achieving the precise adhesion-reducing effect of "high initial tack - low peel", which is especially suitable for the scenarios where temporary fixation and easy removal are required after glass cutting.
[0034] (2) The present invention selects ethyl acetate with low toxicity as the solvent and limits the addition amount of the polymerization inhibitor, which can reduce the volatilization and residue of harmful substances during production and use, meeting the requirements of green manufacturing. At the same time, the staged feeding and temperature control optimize the reaction stability and reduce the safety risk of the production process.
[0035] (3) In the present invention, 3,4-epoxycyclohexyl methacrylate and boron trifluoride catalyst are introduced. Through the efficient cross-linking reaction of epoxy groups, a dense polymer network is formed, significantly enhancing the cohesive strength and heat resistance of the adhesive. It can withstand the reaction heating conditions of 80 - 90 °C, ensuring its performance stability under high temperature or mechanical stress.
[0036] (4) By precisely regulating the mass ratio of acrylate monomers in the present invention, preferably with the mass ratio of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate being (80 - 90):(200 - 240):(30 - 45):(50 - 75):(10 - 30), the adhesive can be endowed with excellent flexibility and interfacial wetting ability. The product is suitable for the surfaces of various substrates such as glass, metal, and polymer materials, and can reduce substrate damage or residual glue problems caused by stress concentration.
[0037] (5) In the preparation process of the present invention, a process step of feeding materials in stages and adding initiators in multiple batches is adopted, and the reaction temperature and reaction time of each stage are further defined to ensure the full progress of the free radical polymerization reaction, avoid local overheating or the residue of unreacted monomers, and finally obtain an adhesive product with a uniform molecular weight distribution and stable performance, significantly improving the consistency of mass production batches. Detailed Embodiments
[0038] Example 1
[0039] In the first aspect of this example, a glass-cutting UV adhesion-reducing adhesive is provided. Its preparation raw materials are as follows by mass: 402.75 g of acrylate monomers, 2.25 g of acrylic acid monomer, 4.5 g of initiator, 536.05 g of solvent, 45 g of epoxy acrylate, 9 g of catalyst, and 0.45 g of inhibitor.
[0040] The acrylic acid monomer is as follows by mass: 81 g of n-butyl acrylate, 67.5 g of 2-hydroxyethyl methacrylate, 202.5 g of isooctyl acrylate, 33.75 g of butyl methacrylate, and 18 g of isobornyl acrylate.
[0041] The acrylic acid monomer is methacrylic acid.
[0042] The initiator is benzoyl peroxide.
[0043] The solvent is ethyl acetate.
[0044] The epoxy acrylate is 3,4-epoxycyclohexyl methacrylate.
[0045] The catalyst is boron trifluoride.
[0046] The inhibitor is p-methoxyphenol.
[0047] The second aspect of this example provides a method for preparing a glass-cutting UV tackifier adhesive, specifically as follows:
[0048] S1. Mix methacrylic acid, n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate evenly to obtain a mixture of methacrylic acid and acrylate monomers. Divide it into two equal parts on average. Take one part and put it at the bottom of the reaction kettle. Add 202.5 g of ethyl acetate and 1.8 g of benzoyl peroxide, control the reaction temperature at 80 °C, and keep the reaction for 2.5 h with heat preservation.
[0049] S2. Then, dropwise add the other part of the mixture of methacrylic acid and acrylate monomers and 177.5 g of ethyl acetate solvent over 3 h.
[0050] S3. Then, dropwise add 25 g of ethyl acetate and 1.8 g of benzoyl peroxide over 20 min. After the addition is complete, keep the reaction for 30 min at 80 °C with heat preservation.
[0051] S4. Then, add 25 g of ethyl acetate and 0.45 g of benzoyl peroxide in one batch, and keep the reaction for 2 h at 80 °C with heat preservation.
[0052] S5. Then, add 25 g of ethyl acetate and 0.45 g of benzoyl peroxide in one batch, and keep the reaction for 3 h at 85 °C with heat preservation.
[0053] S6. After the reaction is completed, add 25 g of ethyl acetate, cool to 25 °C, and let it stand for 24 h.
[0054] S7. Restart the reaction kettle, heat up to 80 °C, and sequentially add p-methoxyphenol, 3,4-epoxycyclohexylmethyl methacrylate, boron trifluoride, and 56.05 g of ethyl acetate, and react for 9 h. After the reaction is completed, cool to 25 °C and discharge to obtain the product.
[0055] Example 2
[0056] The first aspect of this example provides a glass-cutting UV tackifier adhesive. Its preparation raw materials are as follows by mass: 410 g of acrylate monomer, 3 g of acrylic acid monomer, 4.5 g of initiator, 536.05 g of solvent, 45 g of epoxy acrylate, 9 g of catalyst, and 0.45 g of inhibitor.
[0057] The acrylic acid monomer is as follows by mass: 80 g of n-butyl acrylate, 70 g of 2-hydroxyethyl methacrylate, 210 g of isooctyl acrylate, 30 g of butyl methacrylate, and 20 g of isobornyl acrylate.
[0058] The acrylic acid monomer is methacrylic acid.
[0059] The initiator described above is benzoyl peroxide.
[0060] The solvent described above is ethyl acetate.
[0061] The epoxy acrylate described above is 3,4-epoxycyclohexyl methacrylate.
[0062] The catalyst described above is boron trifluoride.
[0063] The inhibitor described above is p-methoxyphenol.
[0064] The second aspect of this example provides a preparation method of a glass cutting UV tackifying adhesive, specifically as follows:
[0065] S1. Mix methacrylic acid, n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate evenly to obtain a methacrylic acid and acrylate monomer mixture. Divide it into two equal parts on average. Take one part and put it into the bottom of the reaction kettle. Add 202.5 g of ethyl acetate and 1.8 g of benzoyl peroxide, control the reaction temperature at 80 °C, and keep the reaction for 2.5 h;
[0066] S2. Then dropwise add the other part of the methacrylic acid and acrylate monomer mixture and 177.5 g of ethyl acetate solvent, and the dropping time is 3 h;
[0067] S3. Then dropwise add 25 g of ethyl acetate and 1.8 g of benzoyl peroxide, and the dropping time is 20 min. After the dropping is completed, keep the reaction at 80 °C for 30 min;
[0068] S4. Then add 25 g of ethyl acetate and 0.45 g of benzoyl peroxide in one batch, and keep the reaction at 80 °C for 2 h;
[0069] S5. Then add 25 g of ethyl acetate and 0.45 g of benzoyl peroxide in one batch, and keep the reaction at 85 °C for 3 h;
[0070] S6. After the reaction is completed, add 25 g of ethyl acetate, cool to 25 °C, and let it stand for 24 h;
[0071] S7. Restart the reaction kettle, heat up to 80 °C, and successively add p-methoxyphenol, 3,4-epoxycyclohexyl methacrylate, boron trifluoride, and 56.05 g of ethyl acetate, and react for 9 h. After the reaction is completed, cool to 25 °C and discharge to obtain the product.
[0072] Comparative Example 1
[0073] In the first aspect of this example, a glass-cutting UV adhesion-reducing adhesive is provided. The preparation raw materials, by mass, are specifically: 402.75 g of acrylate monomer, 2.25 g of acrylic acid monomer, 9 g of initiator, 535.6 g of solvent, 45 g of epoxy acrylate, 4.5 g of catalyst, and 0.45 g of inhibitor.
[0074] The acrylic acid monomer, by mass, is specifically: 209.25 g of n-butyl acrylate, 54 g of 2-hydroxyethyl methacrylate, 90 g of isooctyl acrylate, 31.5 g of butyl methacrylate, and 18 g of isobornyl acrylate.
[0075] The acrylic acid monomer is methacrylic acid.
[0076] The initiator is benzoyl peroxide.
[0077] The solvent is ethyl acetate.
[0078] The epoxy acrylate is 3,4-epoxycyclohexylmethyl methacrylate.
[0079] The catalyst is boron trifluoride.
[0080] The inhibitor is p-methoxyphenol.
[0081] In the second aspect of this example, a preparation method of a glass-cutting UV adhesion-reducing adhesive is provided, specifically:
[0082] S1. Mix methacrylic acid, n-butyl acrylate, isooctyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and isobornyl acrylate evenly to obtain a mixture of methacrylic acid and acrylate monomers. Divide it into two equal parts on average. Take one part and put it at the bottom of the reaction kettle, add 202.5 g of ethyl acetate and 3.6 g of benzoyl peroxide, control the reaction temperature at 85 °C, and keep the reaction for 3 h;
[0083] S2. Then dropwise add the remaining mixture of methacrylic acid and acrylate monomers and 177.5 g of ethyl acetate solvent, and the dropping time is 3.5 h;
[0084] S3. Then dropwise add 25 g of ethyl acetate and 3.6 g of benzoyl peroxide, and the dropping time is 20 min. After the dropping is completed, keep the reaction at 85 °C for 30 min;
[0085] S4. Then add 25 g of ethyl acetate and 0.9 g of benzoyl peroxide in one batch, and keep the reaction at 85 °C for 2 h;
[0086] S5. Then add 25 g of ethyl acetate and 0.9 g of benzoyl peroxide in one batch, and keep the reaction at 85 °C for 3 h;
[0087] S6. After the reaction is completed, add 25 g of ethyl acetate, cool to 25 °C, and let stand for 24 h;
[0088] S7. Reopen the reaction kettle, heat up to 70 °C, and successively add p-methoxyphenol, 3,4-epoxycyclohexyl methacrylate, boron trifluoride and 55.6 g of ethyl acetate, react for 9 h. After the reaction is completed, cool to 25 °C and discharge to obtain the product.
[0089] Performance Test
[0090] 1. Bonding Performance Test
[0091] Test Object: The glass cutting UV adhesives prepared in Examples 1-2 and Comparative Example 1.
[0092] Test Method: Apply the glass cutting UV adhesive on the coating film, stick it on the stainless steel plate, and after 20 min, test the peel strength. The test results are shown in Table 1; the appropriate range of peel strength is 1000-1500 gf.
[0093] 2. Tack Reduction Performance Test
[0094] Test Object: The glass cutting UV adhesives prepared in Examples 1-2 and Comparative Example 1.
[0095] Test Method: Apply the glass cutting UV adhesive on the coating film, perform UV light curing, and test the tack reduction performance according to the national standard GB / T 2792-2014. The UV tackiness less than 15 gf is qualified. The test results are shown in Table 1.
[0096] 3. Residual Adhesive Test
[0097] Test Object: The glass cutting UV adhesives prepared in Examples 1-2 and Comparative Example 1.
[0098] Test Method: Apply the glass cutting UV adhesive on the coating film, stick it on the stainless steel plate, peel it off after 24 h, and observe whether there is residual adhesive on the surface. The test results are shown in Table 1.
[0099] Table 1
[0100] Label Peeling force Adhesion after UV Residual glue test Example 1 1200 gf 12 gf No residual glue Example 2 1300 gf 13 gf No residual glue Comparative Example 1 850 gf 25 gf No residual glue
[0101] It can be seen from the experimental results in Table 1 that the glass cutting UV tack reduction adhesive prepared by the present invention has excellent bonding performance, low tackiness after UV light irradiation, significant tack reduction performance, and is not easy to produce residual adhesive after the glass cutting UV adhesive film is peeled off, and the actual use effect is excellent.
Claims
1. A glass cutting UV viscosity reducing adhesive, characterized in that: The raw materials for preparation include, by weight, 1-5 parts of methacrylic acid, 300-500 parts of acrylate monomers, 40-80 parts of epoxy acrylate, 3-8 parts of initiator, 500-1000 parts of solvent, 5-20 parts of catalyst, and 0.1-1 part of inhibitor.
2. The glass cutting UV viscosity reducing adhesive according to claim 1, characterized in that: The mass ratio of the methacrylic acid, acrylate monomer and epoxy acrylate is (2-3): (350-420): (40-50).
3. The glass cutting UV viscosity reducing adhesive according to claim 2, characterized in that: The acrylic acid ester monomers include one or more of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, hydroxyethyl methacrylate, isobornyl acrylate, hydroxyethyl acrylate, glycidyl acrylate, methyl methacrylate, ethylene glycol diacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate.
4. The glass cutting UV viscosity reducing adhesive according to claim 3, characterized in that: The acrylic acid ester monomers include n-butyl acrylate, isooctyl acrylate, butyl methacrylate, hydroxyethyl methacrylate, and isobornyl acrylate; The mass ratio of n-butyl acrylate, isooctyl acrylate, butyl methacrylate, hydroxyethyl methacrylate and isobornyl acrylate is (80-90): (200-240): (30-45): (50-75): (10-30).
5. The glass cutting UV viscosity reducing adhesive according to claim 2, characterized in that: The epoxy acrylate includes one or more of 3,4-epoxycyclohexyl methacrylate, 1,2-epoxycyclohexyl methacrylate, dicyclopentadiene epoxy methacrylate, bisphenol A epoxy acrylate, and 3,4-epoxytetrahydrofuran methacrylate.
6. The glass cutting UV viscosity reducing adhesive according to any one of claims 1 to 5, characterized in that: The initiator includes one or more of ammonium persulfate, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and azobisisobutyronitrile.
7. The glass cutting UV viscosity reducing adhesive according to claim 1, characterized in that: The solvent includes one or more of toluene, dichloromethane, ethyl acetate, chloroform, acetone and n-butanol.
8. The glass cutting UV viscosity reducing adhesive according to claim 1, characterized in that: The catalyst comprises one or more of boron trifluoride, N,N-dimethylaniline, tetramethylthiourea, N,N-dimethylbenzylamine, 2-methylpyridine and tetramethylammonium chloride.
9. The glass cutting UV viscosity reducing adhesive according to claim 1, characterized in that: The polymerization inhibitor comprises one of hydroquinone, p-hydroxyanisole, hydroquinone and hydroquinone monomethyl ether.
10. A method for preparing the glass cutting UV viscosity reducing adhesive according to any one of claims 1 to 9, characterized in that: include: Firstly, methacrylic acid and acrylate monomers are mixed, and then epoxy acrylate, initiator, solvent, catalyst and inhibitor are added to react to obtain the product.
Citation Information
Patent Citations
Viscosity-reduced pressure-sensitive adhesive and preparation method thereof
CN110628333A